Mencegah Pelecehan Seksual Pada Anak Dengan Pendidikan Kesehatan Reproduksi dan Seksualitas Sejak Dini - Wardatul Karomah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
Children and youth are prone to misinformation about sex. If they do not get proper sex education, they will be consumed with false myths about sex. Information about sex should be obtained directly from parents who have special attention to their children. The parental role in providing sex education we can tell the children that sex is something natural and natural happened to all people, in addition children can also be told about risky sexual behavior so they can avoid it. The purpose of sexual education is to create a healthy emotional attitudes toward sexual problems and guide children and adolescents toward a healthy adult life and responsible for his sexual life. In children aged under five, the way we as parents in providing sexual education in children can begin to instill sex education. The way is quite easy, that is by starting to introduce to the small sex organs hers in brief.